2007
DOI: 10.1126/science.1149802
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Coherent THz Radiation from Superconductors

Abstract: Compact solid-state sources of terahertz (THz) radiation are being sought for sensing, imaging, and spectroscopy applications across the physical and biological sciences. We demonstrate that coherent continuous-wave THz radiation of sizable power can be extracted from intrinsic Josephson junctions in the layered high-temperature superconductor Bi 2 Sr 2 CaCu 2 O 8 . In analogy to a laser cavity, the excitation of an electromagnetic cavity resonance inside the sample generates a macroscopic coherent state in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
692
6
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 724 publications
(738 citation statements)
references
References 29 publications
(24 reference statements)
31
692
6
4
Order By: Relevance
“…An interesting characteristic feature of this EM emission lies in a monochromatic spectrum [1,2]. The line width is so sharp that the observed line width of radiation is limited by the resolution of our conventional spectrometers which has 0.25 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting characteristic feature of this EM emission lies in a monochromatic spectrum [1,2]. The line width is so sharp that the observed line width of radiation is limited by the resolution of our conventional spectrometers which has 0.25 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have succeeded in generating intense, coherent, continuous and monochromatic electromagnetic (EM) waves in the THz frequency region emitted from the mesa structure fabricated on the single crystalline high-T c superconductor Bi 2 Sr 2 CaCu 2 O 8+d , which is known as a typical intrinsic Josephson junction system [1,2]. Here, we provide further detailed information on such fascinating phenomenon generating EM waves at THz frequencies mainly from experimental point of view in order to make it clear the mechanism of the emission.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the non-uniform S/FI/S junction, several applications such as spin-current emitter by utilizing spin-wave excitation in the FI 41 may be also possible in analogy with the emission of coherent THz radiation in the high-T c cuprate, [42][43][44] 7/10…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In fact, the inhomogeneity of the junction was one of essential factors to realize the emission without external magnetic field. [42][43][44] However, novel devices using the S/FI/S junction are beyond the scope of the present paper and will be studied elsewhere.…”
mentioning
confidence: 99%
“…The frequency and the junction voltage proportionality is a promising fact for the design of frequency-tunable radiation sources. Ozyuzer et al successfully [6] observed directly the strong emission of electromagnetic waves using a mesa of Bi2212 crystal in the absence of an external magnetic field; the mesa shaped THz device with sizable power works as a dc voltage to high frequency converter.…”
Section: Introductionmentioning
confidence: 99%